Image Encryption Model based on Chaotic Henon Map and Termite Alate Optimization Algorithm - Kumar, Naveen; Saini, Satish (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the present era, data communication in the form of multimedia images is increasing on the internet. To secure it, an image encryption model is designed in this paper. To accomplish this goal, multimedia images are encrypted using random keys. The random keys are generated using the chaotic Henon map algorithm.It is a two-dimensional signal. Hence, 2-D key generation is possible from it. The chaotic henon map is sensitive to input parameters, and the determination of its optimal value generates a completely random key. However, it is a complex process to search the values in the lower and upper bounds of the parameter value. To accomplish this goal, metaheuristic algorithms are used in the literature. Metaheuristics is a field of optimization. Thus, these algorithms, based on a given problem, find the optimal solution. In this paper, we have used a recent termite alate optimization algorithm based on the photoactivity of the termites that is characterized according to the requirements in the proposed model. After key generation, exclusive-OR and permutation steps are performed for final encryption. The simulation evaluation of the proposed model is based on the different gray-scale images. Further, subjective, and objective parameters are determined for it. The result shows that the proposed model achieves high entropy near 8 values, a low correlation coefficient near 0 values, and a low PSNR.